2013
DOI: 10.3109/10826084.2012.754899
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parental Alcoholism, Sense of Belonging, and Resilience on Depressive Symptoms: A Path Model

Abstract: This paper explored the relationships between parental alcoholism, sense of belonging, resilience, and depressive symptoms in Koreans in the U.S. Data from 206 Koreans (Mean age = 28.4 years; 59.8% females) living in a Midwestern state were collected in 2009, using a web-based survey, which included Children of Alcoholic Screening Test, Sense of Belonging Instrument, Connor–Davidson Resilience Scale, and Beck Depression Inventory-II. Path analysis results revealed sense of belonging as the most powerful, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…According to this finding, even if an individual's psychological resilience is few studies toward increasing the individual's self-esteem will be important in the following years. There is a strong relation between resilience and self-esteem (Eraslan, 2014;Lee & Williams, 2013;Sarıkaya, 2015;Sart, Börkan, Erkman, & Serbest, 2016). Hence, the increase in self-esteem will increase the resilience of an individual.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…According to this finding, even if an individual's psychological resilience is few studies toward increasing the individual's self-esteem will be important in the following years. There is a strong relation between resilience and self-esteem (Eraslan, 2014;Lee & Williams, 2013;Sarıkaya, 2015;Sart, Börkan, Erkman, & Serbest, 2016). Hence, the increase in self-esteem will increase the resilience of an individual.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…As the number of childhood adverse events increases, the risk of alcoholism and depression in those who grew up in alcoholic families increases (Anda et al, 2002). As reported in our previous studies, however, the negative consequences related to parents' alcohol problems and the number of adverse experiences in ACOAs' childhood have also been found to decrease as resilience and/or sense of belonging increase (Lee & Cranford, 2008;Lee & Williams, 2013). Specifically, resilient ACOAs are more likely to have tolerance of negative effect by developing better problem-solving or coping skills or positive acceptance of change (Lee & Williams, 2013).…”
Section: Introductionmentioning
confidence: 56%
“…As reported in our previous studies, however, the negative consequences related to parents' alcohol problems and the number of adverse experiences in ACOAs' childhood have also been found to decrease as resilience and/or sense of belonging increase (Lee & Cranford, 2008;Lee & Williams, 2013). Specifically, resilient ACOAs are more likely to have tolerance of negative effect by developing better problem-solving or coping skills or positive acceptance of change (Lee & Williams, 2013). In addition, feeling valued and connected within a social system can help the individual to recognize more positive aspects in their lives and reduce potential deleterious effects of any sustained stress (Hagerty & Patusky, 1995;Lee & Williams, 2013).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In another study, Lee 23 explored sense of belongingness, resilience and depressive symptoms among alcoholics and non-alcoholics. The findings revealed that on depressive symptoms, alcoholics scored significantly higher than non-alcoholics.…”
mentioning
confidence: 99%